EVALUASI TATA LETAK FASILITAS PRODUKSI UNTUK MENINGKATKAN EFISIENSI KERJA PADA PT. NUSA MULTILAKSANA - Hesti Maheswari; Achmad Dany Firdauzy (Universitas Mercu Buana, 2015)
This study aimed to evaluate the production floor layout PT.Nusa Multilaksana. This study discusses the material handling and production facility layout PT.Nusa Multilaksana. Authors limit the scope of the problem by simply discussing the total cost of material handling and movement. The analytical tool used is the algorithm CRAFT. CRAFT method as one of the layout algorithm improvement used in this study, which provide the best solutions in the rearrangement of the layout of the company. The analysis showed that the total moment of transfer of the initial layout of 85675.9 meters, after repair and adjustment using CRAFT algorithm, the total moment displacement distance of 81429.9 meters or happen savings of 5% of the initial layout.Total cost of material handling initial layout that is equal Rp.48.407.800, after repair and adjustment using CRAFT algorithm, the total material handling costs by Rp.34.099.680 or be saving 30% of the initial layout.The total time of the initial movement of the initial layout 288 581 seconds, after repair and adjustment using CRAFT algorithm, the total time of the movement of 265 266 seconds or occurs savings of 8% of the initial layout.Keywords : Material Handling, Layout, CRAFT